Assessing drought resilience through morphological adaptations and survivability of citrus rootstocks (Indian Journal of Arid Horticulture, 2025)
Understanding rootstock-specific morphological responses is key to selecting resilient genotypes for water-limited orchards. A controlled pot experiment was conducted during the year 2024–25 at Banda University of Agriculture and Technology, Banda, using seven citrus rootstocks (Rangpur lime, Cleopatra mandarin, Rough lemon, Sour orange, NRCC RS-3, RS-4, RS-6) subjected to four water stress levels (control, 0.4, 0.6, and 0.8 bar) for 240 days. Plant mortality increased with stress, reaching 55.16% at 0.8 bar, with Cleopatra mandarin showing the highest mortality at 88.89%. Compared to the control, plant height, stem diameter, leaf number, leaf area, and root length declined by 26.1%, 26.3%, 46.8%, 15%, and 32%, respectively, at 0.8 bar. Rough lemon and Rangpur lime performed better, maintaining heights of 56.24 cm and 54.02 cm, leaf areas of 25.57 cm² and 23.64 cm², and root lengths of 28.02 cm and 25.94 cm. Significant interactions were noted in canopy traits, with Rough lemon having the highest leaf number (127.58) and minimal loss (45.9%), while Cleopatra mandarin showed the greatest canopy reduction (52.5% leaf loss). Although root length interactions were non-significant, Rough lemon had the least reduction (27.8%) under stress, indicating strong root plasticity. Rough lemon, Sour orange, and Rangpur lime exhibited superior drought resilience through greater canopy retention and root plasticity. These rootstocks are promising candidates for improving drought tolerance and sustaining productivity in water-limited citrusorchards.